The Study of Monetary Policy, Exchange Rate and Gold Effects on the Stock Market in Iran Using MS-VAR-EGARCH Model - Khalil Jahangiri; Seyed Ali Hoseini Ebrahimabad (تحقیقات مالی, 2017)
The main objective of this research is to investigate the effects of previous and current changes in monetary policy, foreign exchange market and gold-coin market on the overall performance of Tehran Stock Market. For this purpose, monthly reports of liquidity, exchange rate, gold-coin price and Tehran Stock Exchange Index were collected in the period from April 2001 to March 2017. The data were then analyzed using the MS-VAR and EGARCH approaches. The results of the estimation of the research model showed that in a model with two regimes, the former exchange rate return has a significantly positive effect on the return of stock market index and there is a significantly negative relationship between the performance of the stock market index and gold coin return in the regime one. Regarding the regime zero, the results were indicative of a positive and significant relationship between the past values of liquidity growth and the return of the stock market index. The results also showed that current shocks of exchange rate and liquidity have a significantly negative effect on the returns of Tehran stock exchange index.